On occurrence of some avian bacterial diseases and biosafety provision - T. V. Kurmakaeva; S. S. Kozak; E. S. Baranovich (Ветеринария сегодня)
The proportion of infectious diseases in general avian pathology is known to vary significantly, while bacterial infections play a critical role in avian disease occurrence and incidence. Most of them are registered in the country’s large-scale poultry holdings, poultry farms and backyards and pose a serious risk in terms of epidemic and veterinary-sanitary aspects. This paper presents the results of analysis of avian colibacillosis and salmonellosis occurrence in 2018–2022, taking into account the number of outbreaks and diseased poultry for each disease. A retrospective analysis showed that these infections are registered annually in poultry farms of the Russian Federation, within a 5-year-period the number of poultry with colibacillosis ranged from 66.18% in 2018 to 0.15% in 2021 of the total number of diseased birds, and the number of Salmonella-infected poultry ranged from 65.91% in 2019 to 0.57% in 2021. In 2018–2020 219,020 samples of poultry meat and poultry products were tested for Salmonella, while Salmonella enteritidis, Salmonella typhimurium, Salmonella infantis were detected in 0.80% cases. It should be noted that in accordance with the requirements of Technical Regulations TR CU 021/2011 and TR EAEU 051/2021, no Salmonella is allowed in 25 g of poultry meat. According to the VESTA automated system, during the study period, incompliances with microbiological safety parameters were detected in 16.11% of poultry meat and poultry product samples, of which 10.98% of the samples contained mesophilic aerobic and facultative anaerobic microorganisms, and 5.13% contained Escherichia coli. The data obtained indicate the need for a retrospective analysis of the occurrence of some avian bacterial infections in order to study the animal disease situation in poultry farms for the purpose of improving the set of measures to ensure the disease freedom in poultry industry, while addressing the laboratory test results.